If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(2c + 4) = 0 Reorder the terms: 8(4 + 2c) = 0 (4 * 8 + 2c * 8) = 0 (32 + 16c) = 0 Solving 32 + 16c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + 16c = 0 + -32 Combine like terms: 32 + -32 = 0 0 + 16c = 0 + -32 16c = 0 + -32 Combine like terms: 0 + -32 = -32 16c = -32 Divide each side by '16'. c = -2 Simplifying c = -2
| 84=4v-2(X-3)-3x | | 160+170+400+x=1000 | | 128=2n+8(n+6v) | | 5/9d=9/4 | | 11x+3=10x+3 | | (3/7)x-1=(2/3)(6x-2) | | (3/7)x-1=(⅔)(6x-2) | | 83=2(-6b+1)-3 | | (3/7)x-1=(2/ | | 11k=13t−7k/2t | | 1+Log[5](-4x)=3 | | 544=-5n-8(7n-7) | | (3z-5)(7-z)=0 | | 2/3y-6=10 | | 3x-4(-2x-5)=2x-3 | | 5x^2+6-51=0 | | h-4+1=3 | | 8(3x-5)=-64 | | ln(17+2x)=2ln(x+1) | | 7/7=3 | | -2x-5(4x+3)=3x | | 26=10h/18 | | 11.5x+12=161.50 | | 3(-2y)+7y=1 | | 5t=56 | | c=12+11.5t | | 9x-6(x-2)=6+x+20 | | (9x-6)+(-8x+4)=7 | | 2x+x^2=0.051216343 | | sqrt(60)*sqrt(y/4) | | v/9=3/7 | | (4a+4b+4c)(4a+4b+4c)= |